Kontribusi Usaha Kuliner PKK Dusun Diro terhadap Penguatan Ekonomi Pariwisata Berbasis Komunitas di Kalurahan Pendowoharjo - Atun Yulianto; R. Jatinurcahyo; Yulianto (Journal of Tourism and Economic, 2025)
This study aims to examine the contribution of the culinary enterprise managed by PKK Sirkoyo 2 in Diro, Pendowoharjo Village, Bantul, to strengthening the community-based tourism economy. A qualitative case study approach with descriptive analysis was employed. The findings indicate that the production of traditional food not only increases household income but also enhances women’s participation in local economic activities. The culinary products have been integrated into various cultural events at the village level and attract tourists through their distinctive tastes and traditional presentation. This initiative contributes to cultural preservation while expanding women's access to public and economic spaces. Although several challenges remain such as limited production equipment and insufficient access to digital marketing the enterprise holds strong development potential through training support and collaboration with village tourism stakeholders. These findings underscore the importance of empowering women through the culinary sector as a strategic component of inclusive and sustainable community-based tourism development.